High-purity hydrogen production by sorption-enhanced steam reforming of iso-octane over a Pd-promoted Ni-Ca-Al-O bi-functional catalyst. (1st June 2021) - Dang, Chengxiong; Li, Hanke; Yang, Guangxing; Cao, Yonghai; Wang, Hongjuan; Peng, Feng; Wang, Songrui; Yu, Hao
Graphical abstract: Highlights: 98.5% hydrogen is produced from sorption-enhanced steam reforming of iso -octane. 90% hydrogen yield was achieved for 10 SESRI-decarbonation cycles. The SESRI reaction lowered the reaction temperature by >200 °C. Abstract: Liquid hydrocarbon fuels produced from fossil resources are potential portable hydrogen carriers given their sufficient supply and extensively available infrastructures. However, effective approaches to hydrogen production from liquid hydrocarbons fuels are still insufficient, especially in the context of carbon emission control. Here, we report that high-purity hydrogen is produced with minimized CO2 emissions via the sorption enhanced steam reforming of iso -octane (SESRI), a model compound of gasoline. With a Pd-promoted Ni-CaO-Ca12 Al14 O33 bi-functional catalyst, 98.0% purity of hydrogen with 90% hydrogen yield was obtained for 10 consecutive SESRI-decarbonation cycles. XRD, SEM, and TEM techniques revealed that structural and morphological properties of the bi-functional catalyst were preserved after 10 cycles. Raman spectroscopy, CO2 -TPO and TGA further demonstrated that coke formation was substantially suppressed in the presence of Pd, which played a key role in maintaining stable SESRI performance in terms of hydrogen production. Our results provide a feasible alternative for production of high-purity hydrogen from liquid fossil fuels, thereby being prospective in meeting the demand of portable hydrogen on short to medium term basis.